Olive Ridley comes home - Garlitos, Rhandee; Doctor, Yasmin; Tamayo, Faith (Quezon City LG & M Corporation, 2013)
"Olive Ridley will lay her eggs for the first time. Like many sea turtles around the world, she has to return to her birthplace and leave her eggs there. She sets off for nagbalayong amidst the perils of the sea, especially humans whose nets trap sea creatures. On her way,, Olive gets caught in the net of a fisherman and his son. Will she able to escape, or are she and her children doomed?"
"Ages 7-13 y.o."
Text in English and Filipino.
Keywords: Turtles -- Juvenile fiction; Children's stories, Philippine (English)